Requirements for Additional Strength Biowaivers for Modified Release Solid Oral Dosage Forms in International Pharmaceutical Regulators Programme Participating Regulators and Organisations: Differences and Commonalities - Matthias Shona Roost; Henrike Potthast; Chantal Walther; Alfredo García-Arieta; Ivana Abalos; Eduardo Agostinho Freitas Fernandes; Gustavo Mendes Lima Santos; Zulema Rodríguez Martínez; Andrew Tam; Clare Rodrigues; Diego Alejandro Gutierrez Triana; Erwin Guzmán Aurela; et al. (Frontiers Media S.A., 2021)
This article describes an overview of waivers of in vivo bioequivalence studies for additional strengths in the context of the registration of modified release generic products and is a follow-up to the recent publication for the immediate release solid oral dosage forms. The current paper is based on a survey among the participating members of the Bioequivalence Working Group for Generics (BEWGG) of the International Pharmaceutical Regulators Program (IPRP) regarding this topic. Most jurisdictions consider the extrapolation of bioequivalence results obtained with one (most sensitive) strength of a product series as less straightforward for modified release products than for immediate release products. There is consensus that modified release products should demonstrate bioequivalence not only in the fasted state but also in the fed state, but differences exist regarding the necessity of additional multiple dose studies. Fundamental differences between jurisdictions are revealed regarding requirements on the quantitative composition of different strengths and the differentiation of single and multiple unit dosage forms. Differences in terms of in vitro dissolution requirements are obvious, though these are mostly related to possible additional comparative investigations rather than regarding the need for product-specific methods. As with the requirements for immediate release products, harmonization of the various regulations for modified release products is highly desirable to conduct the appropriate studies from a scientific point of view, thus ensuring therapeutic equivalence.